2016
DOI: 10.1016/j.braindev.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of genetic alterations in early-onset epileptic encephalopathies associated with infantile movement disorders

Abstract: We found pathogenic mutations in seven genes, in nine of 11 patients with EOEE and involuntary movements. Although the results of our study are preliminary because of the small number of patients, they nevertheless suggest that specific accompanying phenotypes such as hyperkinetic movements or hand stereotypies could be important in narrowing the disease spectrum and identifying causative genetic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 43 publications
6
82
0
1
Order By: Relevance
“…CDKL5 gene is located on the X chromosome, and the majority of reports describe de novo X-linked variants in females4345, here, we identified a variant in a male patient, which spots the lights on the potential under-recognition of CDKL5 gene mutation as a pathogenic variant in males, which has been recently emphasized2830. Previously reported studies have shown that patients with CDKL5 variants are mainly presented as early onset epileptic encephalopathy (EOEE) with epileptic spasms and severe ID, and suggested that CDKL5 variants should be kept in consideration first in patients showing EOEE with involuntary movements which is being advised by our results which is being enforced by our results283046.…”
Section: Discussionsupporting
confidence: 62%
“…CDKL5 gene is located on the X chromosome, and the majority of reports describe de novo X-linked variants in females4345, here, we identified a variant in a male patient, which spots the lights on the potential under-recognition of CDKL5 gene mutation as a pathogenic variant in males, which has been recently emphasized2830. Previously reported studies have shown that patients with CDKL5 variants are mainly presented as early onset epileptic encephalopathy (EOEE) with epileptic spasms and severe ID, and suggested that CDKL5 variants should be kept in consideration first in patients showing EOEE with involuntary movements which is being advised by our results which is being enforced by our results283046.…”
Section: Discussionsupporting
confidence: 62%
“…IEM may be heralded by a number of suggestive clinical features including neonatal encephalopathy, neurological regression after a period of typical development, or clinical deterioration after intercurrent illness or starvation. 18,19 Mitochondrial disorders, such as POLG-related disease, can also often present with a combination of epilepsy and atypical movements. For example, blood and urine testing can aid the diagnosis of specific lysosomal storage disorders, 16 while serum transferrin isoelectric focusing is often abnormal in congenital disorders of glycosylation.…”
Section: Epilepsy and Movement Disorders In Inborn Errors Of Metabolismmentioning
confidence: 99%
“…134,135 FOXG1 mutations share some overlapping features with MECP2-related disease. 18,137 PCDH19 mutations, which encodes a protein highly expressed in the brain, important for cell-cell adhesion, axon guidance, and dendrite self-avoidance, 138 are well known to lead to DEE and later-onset epilepsy in females, characterized by focal and/or generalized seizures that typically occur in clusters. 135 Unlike the MECP2 X-linked inheritance pattern (and consequential female predominance) both sexes are relatively equally affected.…”
Section: Epilepsy Syndromes Associated With Prominent Stereotypiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rauch et al (2012) described a new one, Kuechler et al (2015) and Szczałuba et al (2016) described 2 variants each one, and Kobayashi et al (2016) described 1 de novo mutation. These data show that mutations are commonly found in ID.…”
Section: Discussionmentioning
confidence: 99%